Wyoming mountain escape - Scott, Laura, 1961- (Love inspired suspense., 2021)
Just as Chelsey decides to call off her wedding, her soon-to-be husband is shot and killed at the altar. When the bullets start to fly her way, the best man, former Special Ops soldier Duncan, drags her to safety. But with an unknown enemy on their trail, can they survive long enough to find out why she's a target?